The economics of US health reform : a global perspective - Dewar, Diane M. (London ; New York : Routledge, Taylor and Francis Group, 2018)
"The health care field is currently experiencing a great deal of change, including advances in medical technology, the development of new health care financing mechanisms, and the transformation of organizational arrangements.This text studies the health care system in the US, and selected other countries, through the lens of economics and policy. It presents numerous real world examples and biographies of key figures in order to help students to grasp the importance and relevance of health reform and health policy issues. The book conveys the essence of current reform issues in the US, and places them in a global comparative context.The accessible book will be key reading for advanced undergraduates in public health and students in health related graduate courses, including those that come to the subject without much prior knowledge of health economics or other policy methods. "--Provided by publisher.
part I What Is Health Care? / Diane M. Dewar -- chapter 1 Overview of US Health Care System Issues / Diane M. Dewar -- chapter 2 Comparing Health Care Systems / Diane M. Dewar -- part II The Economics Driving Reform Efforts / Diane M. Dewar -- chapter 3 Equity in Health Care / Diane M. Dewar -- chapter 4 Efficiency in Health Care / Diane M. Dewar -- part III Reform in Action / Diane M. Dewar -- chapter 5 International Health System Reforms -- OECD Countries / Diane M. Dewar -- chapter 6 International Health System Reforms -- Developing Countries / Diane M. Dewar -- part IV The US and Beyond / Diane M. Dewar -- chapter 7 National Health Care Reforms -- Before the Affordable Care Act / Diane M. Dewar -- chapter 8 National Health Care Reform -- The Affordable Care Act / Diane M. Dewar -- chapter 9 The Future of Health Reform Nationally and Internationally / Diane M. Dewar.
Keywords: Health care reform -- Economic aspects -- United States; Medical economics -- United States; Medical policy -- Economic aspects -- United States